Hubungan antara Kemampuan Kognitif dengan Kemampuan Turn-Taking Anak Autism di UPT Pusat Layanan Disabilitas dan Pendidikan Inklusif Surakarta - Siswatiananda, Adila; Sudarman, Sudarman (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: Autism is a neurodevelopmental disorder characterized by a lack of social interactin, difficulty in communication, both verbal and nonverbal, and very limited interests and activities. Cognitive is a thinking process, which refers to an individual's capacity to connect, evaluate, and consider. Cognitive abilities can affect children's language, one aspect of language is pragmatics (turn-taking). Objectives: This research aims to determine the relationship between cognitive abilities and the turn-taking ability of children with autism at UPT Pusat Layanan Disabilitas dan Pendidikan Inklusif Surakarta. Methods: The research used a type of quantitative research with a crosssectional design. The sampling technique used was total sampling with a sample size of 38 respondents. Research instruments used to measure cognitive abilities used the Cognitive Linguistic Evaluation instrument and an instrument to measure turn-taking ability used a pragmatics questionnaire. The statistical test used in this research is the Kendall's Tau test. Results: The results of data analysis obtained from cognitive abilities in children with autism are dominated by the category below average (76.3%) and the results of turn-taking ability in children with autism are dominated by the less category (57.9%). Kendall's Tau test results showed p = 0,000 (???????? accepted), with a correlation coefficient (r) = 0,622 which means it has a positive correlation in the strong category. Conclusion: There are relationship between cognitive ability and turntaking ability of children with autism at the UPT Pusat Layanan Disabilitas dan Pendidikan Inklusif Surakarta. Keywords: Cognitive ability, Turn-taking ability, Autism